PENINGKATAN KOMPETENSI GURU AGAMA HINDU DALAM MENYUSUN RPP YANG BERLITERASI PPK HOTS DAN PEMBELAJARAN ABAD 21 ( C4 ) MELALUI FOKUS GRUP DISKUSI - Susilangayoni, Ketut (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The problem presented by the researcher was can Focus Group Discussion (FGD) Improve Competency of Hindu Teacher in Designing Lesson Plan Literated PPK Hots and 21st Century Learning (C4) in Junior High School Trained District of Melaya Subdistrict, Jembrana Regency? Focus of improvement in the study was improving Hindu teacher’s ability in designing lesson plan in form of professional training which was conducted in two cycles. The main objective was to describe improvement of teacher’s ability in designing lesson plan based on the findings in the study, which was shown as follow. There has been an average improvement of teacher’s ability in designing lesson plan from pre-cycle as many as 69.05), the first cycle was 76,60 and the second cycle was 89,90 at excellent category. According to the observation and the data analysis concluded that by Focus Group Discussion (FGD) activity was able to improve competency of Hindu teacher in designing lesson plan in 2019/2020